Metric and validity issues in assessing war-related traumatic exposure - Ajduković, Dean (Array, 2007)
Intensity and structure of exposure to traumatic events is always considered in models of posttraumatic stress. Indicators that best tap the nature of repeated and prolonged traumatic exposure, which is the often case in war, are still not clear. One of the most detailed instruments was used in the Connect study, based on the Life Stressor Checklist-Revised (Wolfe et al, 1997) and included a list of 25 events that people in war situations typically experience. For each item the participants reported: 1) how many times they have experienced it, 2) times of first, last and most difficult exposure, 3) lasting of each of these, 4) distress caused by them, 5) events before, during or after the war. Five indicators of traumatic exposure were developed and their metric properties and validity tested. Analyses on 454 Ss included correlational analysis and testing the congruence of factor structures among criteria. The validity of indicators was assessed using correlation with 3 mental health measures (PTSD, IES score and major depression). It was found that the indicators highly inter-correlated (.85-.97). In a five-factor solution, interpersonal violence, active and passive combat exposure factors were highly congruent for all indicators. The best predictor for current health status was distress of a single most distressing event and number of events experienced in war conditions.